HUBUNGAN KEPATUHAN DIET DIABETES MELLITUS DAN KEKUATAN GENGGAM HANDGRIP DENGAN KADAR GULA DARAH PRALANSIA DI WILAYAH KERJA PUSKESMAS PANDAK 2 - Amalia, Vinka; Fayasari, Adhila (Jurnal Gizi dan Pangan Soedirman, 2025)
Diabetes mellitus is still a disease problem experienced by the pre-elderly and elderly in the Yogyakarta area. Uncontrolled blood sugar levels in people with diabetes mellitus are caused by several factors, including intake, compliance, medication, and quality of grip strength, which describes physical fitness. The purpose of this study was to analyze the relationship between diabetes mellitus diet compliance and handgrip strength with blood sugar levels of pre-elderly in the Pandak 2 Health Center Area. This study employed a cross-sectional design to assess pre-elderly individuals at the Pandak Health Center from September to November 2024. We collected data on diet compliance using a questionnaire, grip strength with a handgrip dynamometer, and instantaneous blood sugar levels with a glucometer. Data were analyzed using chi-square with α (<0.05). Uncontrolled blood sugar levels in this study were 64%, with dietary compliance at 34.4%. There was a significant relationship between DM diet compliance and blood sugar levels (p 0.011), and there was a significant relationship between grip strength and blood sugar levels (p 0.001). Dietary non-compliance affects blood sugar control and pre-elderly people with weak grip strength tend to have poor blood sugar control.